Cannabinoid receptor 2 deficiency exacerbates inflammation and neutrophil recruitment. Issue 5 (25th February 2019) - Kapellos, Theodore S.; Taylor, Lewis; Feuerborn, Alexander; Valaris, Sophia; Hussain, Mohammed T.; Rainger, G. E.; Greaves, David R.; Iqbal, Asif J.
ABSTRACT: Cannabinoid receptor (CB)2 is an immune cell–localized GPCR that has been hypothesized to regulate the magnitude of inflammatory responses. However, there is currently no consensus as to the mechanism by which CB2 mediates its anti‐inflammatory effects in vivo . To address this question, we employed a murine dorsal air pouch model with wild‐type and CB2 −/− 8–12‐wk‐old female and male C57BL/6 mice and found that acute neutrophil and lymphocyte antigen 6 complex, locus C hi monocyte recruitment in response to Zymosan was significantly enhanced in CB2 −/− mice. Additionally, levels of matrix metalloproteinase 9 and the chemokines C‐C motif chemokine ligand (CCL)2, CCL4, and C‐X‐C motif chemokine ligand 10 in CB2 −/− pouch exudates were elevated at earlier time points. Importantly, using mixed bone marrow chimeras, we revealed that the proinflammatory phenotype in CB2 −/− mice is neutrophil‐intrinsic rather than stromal cell–dependent. Indeed, neutrophils isolated from CB2 −/− mice exhibited an enhanced migration‐related transcriptional profile and increased adhesive phenotype, and treatment of human neutrophils with a CB2 agonist blocked their endothelial transmigration. Overall, we have demonstrated that CB2 plays a nonredundant role during acute neutrophil mobilization to sites of inflammation and, as such, it could represent a therapeutic target for the development of novel anti‐inflammatory compounds to treat inflammatory human diseases.—Kapellos, T. S., Taylor, L., Feuerborn, A., Valaris, S., Hussain, M. T., Rainger, G. E., Greaves, D. R., Iqbal, A. J. Cannabinoid receptor 2 deficiency exacerbates inflammation and neutrophil recruitment. FASEB J. 33, 6154–6167 (2019). www.fasebj.org